Analysis on relationship between flexible work arrangements, work life and employees' efficiency: Evidence from Bosnia and Herzegovina's (BiH) IT sector - Ognjen Ridic; Adnan Avdibegovic; Senad Busatlic (Economic Review: Journal of Economics and Business, 2016)
Today's business environment is more dynamic due to vast technological growth. This growth is most visible in the IT industry. Efficiency, together with work-life balance, is found to be one of the most important factors of success at workplace. Positive impacts of work-life balance include: retention of employees towards their employer, better motivation, and increased efficiency due to an increased employee satisfaction. Recent literature findings show a direct positive relationship between efficiency and work-life balance. Flexible work arrangements have positive impact on work-life balance and efficiency. This study analyzes the impact of flexible work arrangements on employees' work- life balance and efficiency, using a non- random convenience sample selected from BiH's IT employees. In the initial phase of data collection, quantitative survey instrument was adopted based on the original one from Mount Holyoke University. It was translated and back translated from English to Bosnian and again back to English and then verified as the part of pilot testing on 40 IT employees. The study was conducted in a cross-sectional time manner in the period June-July 2016. A modified, 18 questions, primary quantitative survey instrument with a 5-point Likert scale was conducted on 503 Bosnian IT employees. Fourteen questions covered inferential and last four descriptive statistics. The study aims to test if there is a significant relationship between flexible work arrangements, work-life balance, and employee efficiency with respect to their gender, age, time they travel to work and their children status. The results indicate that flexible work time and location can have a positive impact on employee work life balance and this opinion is shared by all the employees surveyed. Although 64.80% of participants stated that their work life is balanced with their personal life, there is always place for improvement. Participants agree that better work life balance, caused by flexible work time and flexible work location, will improve their efficiency and reduce stress.
Keywords: J53; M15; 330; IT; efficiency; flexible work arrangements; work-life balance